2015
DOI: 10.1063/1.4914932
|View full text |Cite
|
Sign up to set email alerts
|

Internal transport barrier triggered by non-linear lower hybrid wave deposition under condition of beam-driven toroidal rotation

Abstract: By using gyro-Landau fluid transport model (GLF23), time-dependent integrated modeling is carried out using TRANSP to explore the dynamic process of internal transport barrier (ITB) formation in the neutral beam heating discharges. When the current profile is controlled by LHCD (lower hybrid current drive), with appropriate neutral beam injection, the nonlinear interplay between the transport determined gradients in the plasma temperature (T i,e ) and toroidal velocity (V / ) and the EÂB flow shear (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although several tools have been identified that modify transport directly, the effect of the current profile on transport is large and remains an important transport control feature. Improvement of the plasma performance through active modification of the current density in advanced plasma regimes with ITBs has been the goal of intense research [28][29][30][31][32]. To establish steady state operation of high performance tokamak, real-time control of the plasma current profile will be an essential aspect.…”
Section: Conclusion and Implication Of The Results Application In Pla...mentioning
confidence: 99%
“…Although several tools have been identified that modify transport directly, the effect of the current profile on transport is large and remains an important transport control feature. Improvement of the plasma performance through active modification of the current density in advanced plasma regimes with ITBs has been the goal of intense research [28][29][30][31][32]. To establish steady state operation of high performance tokamak, real-time control of the plasma current profile will be an essential aspect.…”
Section: Conclusion and Implication Of The Results Application In Pla...mentioning
confidence: 99%